Antioxidant capacity of hydroethanolic extracts from Thalassia testudinum and Syringodium filiforme to counteract UVB radiation effects on skin - Fagundo-Mollineda, Adrián; Morales-Aguilera, Ruth Ana; Menéndez-Soto del Valle, Roberto; González-García, Kethia; García-Jiménez, Teidy; Valdés-Iglesia, Olga; Hernández-Rivera, Yasnay; Lorenzo-Luaces, Patricia; Fernández-Perez, Miguel David; Rodríguez-García, María (Revista Ciencias Marinas y Costeras, 2025)
The prevalence of skin diseases related to ultraviolet radiation (UV) from the sun has increased alarmingly. Direct exposure to UV rays significantly reduces the levels of endogenous antioxidants in the skin. The accelerated increase of free radicals triggers the activation of inflammatory processes that damage collagen and elastin fibers, leading to faster photoaging and the long-term development of melanoma-like lesions. However, searching for new natural components and extracts that can restore endogenous antioxidant levels through topical applications offers a promising avenue for effective treatments. This study aims to evaluate the ability of extracts obtained from the marine angiosperm Thalassia testudinum Banks & Sol. ex Koenig and Syringodium filiforme Kützing in Hohenacker to modify oxidative stress markers (MDA, GSH, SOD) in an in vivo model of UVB light-induced skin photodamage. The leaves of both plants were collected in Rincón de Guanabo, Cuba, in November 2022. Both hydroethanolic extracts have a high content of phenolic compounds (18 ± 1.5 and 25.78 ± 0.07 PyE%) and other natural antioxidants that inhibit lipid peroxidation with IC-50 below 0.008 mg/mL. Results also demonstrate the antioxidant capacity of both extracts in restoring oxidative stress indicators, including MDA, GSH, and SOD values, closer to those found in healthy, non-irradiated skin. The extract of T. testudinum has a greater capacity to increase intracellular SOD enzyme levels. The present research suggests that topical treatment may contribute to maintaining antioxidant levels in the skin, thereby reducing the harmful effects of oxidative imbalance and offering a promising prospect for effective therapies.